A Contribution to the Examination of the Significance of Education for Peace in a Frontline Country. A Polemic with Konrad Rejman?s Article "Pedagogy and (Non) Existence - Existential Reflection on Education and Peace" - Kowzan, Piotr (INSTED: Interdisciplinary Studies in Education & Society, 2022)
The purpose of this debate with Konrad Rejman?s article is to expose those parts of his argument that, when viewed critically, lead to a different approach to peace education. One that is concerned with democracy, engages in field and teacher research, and is connected to social movement activity. Additionally, it does not view dialogue as a panacea.